Analisis Semiotika Terhadap Fenomena Bullying Dalam Animasi “A Silent Voice” - Halil Hidayatur Ramadhan; Jupriani Jupriani (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
This research aimed to analyze bullying scenes in "A Silent Voice" animation from Kyoto Animation Studio directed by Naoko Yamada. In this study, the researcher used Roland Barthes Semiotics analysis research method consisted of three analysis meanings which are denotation, connotation, and myth utilized an analysis unit which are some scenes in "A Silent Voice" animation, and used information source in a form of documentation from "A Silent Voice" animation. The research result indicates that "A Silent Voice" movie has bullying scenes which can be categorized into three types namely physical bullying, verbal bullying, and relational bullying. Other than that, "A Silent Voice" animation illustrates that there are still many unjustice and bullying in school. This movie is useful so that people do not ignore bullying cases in school or other places